The effects of different tillage practices on soil properties, yield and pest incidence of various Sweet Corn (Zea Mays L. Var. Saccharata) varieties - Escototo, Angela R.; Cagasan, Ulysses A. (Annals of Tropical Research, 2022)
Conservation tillage is one of the crop production adaptation strategies for conserving soil and mitigating climate change. This study aimed to evaluate the effects of different tillage practices on the yield, soil properties, and pest incidence of corn varieties that would give optimum output. The experiment was laid out in a split-plot arranged in a randomized complete block design with three replications. Zero and minimum tillage served as the main plot, and the different sweet corn varieties as the subplot (T1– Macho F1, T2– Sweet Supreme F1, T3– Purple Magic F1, T4– Hi-Brix XL F1, and T5– Sugar King F1). Results showed that Hi-Brix XL F1 (8t ha-1), Purple Magic F1 (7.44t ha-1), and Macho F1 (7.45t ha-1) obtained high marketable ear yields among the different sweet corn varieties. On the other hand, zero and minimum tillage did not vary significantly in terms of the soil properties, resulting in no yield advantage for sweet corn. This means that sweet corn production can be done either with zero or minimum tillage. In addition, zero tillage practice obtained lower fresh weight (g) of weeds at 15 and 45 days after planting. Weeds were eliminated using non-selective herbicide spray with zero tillage, resulting in lower weed incidence than with minimum tillage where only one plowing and harrowing were done.